2009
DOI: 10.1111/j.1439-0272.1990.tb02013.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of scrotal sonography in infertile men

Abstract: Summary Scrotal sonography with a 7.5 MHz sector scanner was performed on 658 consecutive patients of our infertility clinic. The incidence of pathological findings was unexpectedly high. Forty per cent of the patients revealed pathological structures such as varicoceles (21%), hydroceles (7%), epididymal abnormalities (6%), spermatoceles (6%), intratesticular hyper‐ and hypoechoic changes (4.5%), intratesticular cysts (1%) and tumours or carcinoma in situ (CIS) (0.6%). Sonographic evaluation and measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 20 publications
1
19
1
2
Order By: Relevance
“…The area under the ROC curve (AUC), an indicator of the overall correct classification rate, was higher than 0.5 for the three different parameters. 136 Andrology, 2013, 1, 133-138 classified as "normal" based on palpation of left and right epididymis (Nashan et al, 1990). Epididymis abnormalities consisting in subjective evidence of duct ectasia, partial absence or inflammatory mass like were significantly more frequent in obstructive compared with non-obstructive azoospermia (Moon et al, 2006;Du et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The area under the ROC curve (AUC), an indicator of the overall correct classification rate, was higher than 0.5 for the three different parameters. 136 Andrology, 2013, 1, 133-138 classified as "normal" based on palpation of left and right epididymis (Nashan et al, 1990). Epididymis abnormalities consisting in subjective evidence of duct ectasia, partial absence or inflammatory mass like were significantly more frequent in obstructive compared with non-obstructive azoospermia (Moon et al, 2006;Du et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of testis volume can be accomplished with the use of comparative ovoids, orchidometers (Prader, Rochester, or Takahara) [15], or ultrasonography. Some have found the use of orchidometers to be equally as effective in estimating testicular volumes, at a lower expense [16], than testicular ultrasound [17]. It is our experience, however, that the orchidometer is too insensitive to volume differentials relative to ultrasound to be used routinely in determining growth impairment.…”
Section: Assessment Of Testicular Volumementioning
confidence: 90%
“…Frauscher et al [26] recently studied scrotal ultrasound findings of mountain bikers and found a significantly high incidence of pathology such as epididymal cysts or scrotal calculi [26]. Nashan et al [27] performed ultrasounds on 658 patients in a fertility clinic and identified similar scrotal pathology in 40% of the patients. While no causal relationship may be derived from these two studies, it is curious that cyclists develop similar scrotal pathology as that found in a significant proportion of patients seeking evaluation for infertility.…”
Section: Etiologymentioning
confidence: 97%